PROBLEMATIKA BEBAN KERJA GURU HONORER DI TAMAN KANAK-KANAK - NURIA, RATRI; Aprilianti, Riska (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2023)
: The duties of Teacher include teaching in class, administrative preparation, as well as additional tasks related to professional positions. The variety of duties of Teacher should be balanced with the rights received for the obligations carried out. So far, the teaching profession in Kindergarten is still in the nature of dedication, and the legal basis for acquiring rights and career a qualitative descriptive method to review the workload of honorary teachers in Kindergarten. The focus of this research is honorary teachers in Kindergarten. The focus of this research is on 1) Pedagogical competence; 2) Professional Competence; 3) Personality Competence; 4) Social Competence.